DIVINE VALUE OF INDONESIAN JURISPRUDENCE: A REFLECTION OF PANCASILA JURISPRUDENCE: ILMU HUKUM INDONESIA YANG BERKETUHANAN: SUATU REFLEKSI ILMU HUKUM PANCASILA - Ade Arif Firmansyah; Malicia Evendia (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2023)
This paper aims to examine divine values as a form of reflection on Pancasila values in Indonesian jurisprudence. This study is important considering that the current conditions for the establishment and enforcement of Indonesian law tend to pay little heed to divine values. Using the doctrinal writing method with a conceptual approach it is found that:Jurisprudence which believes in God is a form of reflection of Pancasila values and is part of Pancasila jurisprudence. Jurisprudence which believes in God is closely related to religious principles which in essence want humans to remain in their minds and consciences in living life. The essence of theology in theology of law focuses on strengthening aspects of morality with regard to the immunity of the legal structure, the establishment of legal substance and legal culture